Expectations and Strategies for Managing the Psychosocial Needs of Elderly People at the Tresna Werdha Husnul Khotimah Social Welfare Institution in Pekanbaru - Olintika, Tiwi; Sidiq, Rd. Siti Sofro; Hambali (Journal of Authentic Research, 2026)
The increase in population and neglect of the elderly in recent years has become a widespread phenomenon in Indonesia, especially in urban areas. This is due to crucial factors, particularly economic factors, which affect the fulfillment of the needs of elderly care and nursing within families that are often below the ideal capacity. This study aims to analyze future constructions, expectation dynamics, and strategies for managing psychosocial pressures faced by the elderly at the Tresna Werdha Khusnul Khotimah Social Service Unit in Pekanbaru. The psychosocial pressures referred to are conditions resulting from complex interactions between psychological factors and a social environment that is new or unfamiliar to them due to their separation from their families and the habits they have been accustomed to outside the nursing home. This study uses a phenomenological qualitative design by conducting interviews with 8 informants and direct observation at the social nursing home. The results of the study reveal that the life experiences of the elderly in the institutional system form two fundamentally different patterns of future construction, which are influenced by the presence or absence of a family support network. Elderly people who do not have family ties tend to form a future construction oriented towards life after death, where death is understood as the final horizon that must be prepared for through the strengthening of spiritual practices and self-development. Conversely, elderly people who still have families maintain a future construction oriented towards social reintegration, characterized by preparation for life after death while hoping to return to the bosom of the family. The implications of this study show that hope helps people adapt and remain strong. Therefore, to improve the functioning of social institutions, the paradigm must shift from uniform care to a meaning-based approach.